(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Exclusive breastfeeding is an ideal source of nutrition because its composition is balanced naturally and in accordance with the growth and development of the baby, so that exclusive breast milk is the most perfect food for babies quality and quantity, in addition to being cheap, easy to obtain and also giving can be done at any time of the day, the best and most perfect first food for babies. But in fact there are still many parents who do not give exclusive breastfeeding to their babies because of the lack of knowledge of mothers about the womb of breast milk and most mothers have to leave their babies while working so they do not understand how to breastfeed when leaving their babies. This community service aims to provide information to breastfeeding mothers about the content of breast milk and its benefits for the growth and development of babies and how to store dairy milk (ASIP) for working mothers. The method used in service activities is in the form of counseling (socialization). After educating mothers, it was found that the increase in knowledge of breastfeeding mothers related to exclusive breastfeeding so that it is hoped that the coverage of exclusive breastfeeding is successful so that the baby’s growth and development can be optimal.